2021
DOI: 10.1111/nin.12460
|View full text |Cite
|
Sign up to set email alerts
|

Living alone and using social media technologies: The experience of Filipino older adults during the COVID‐19 pandemic

Abstract: Prolonged implementation of lockdowns during the coronavirus disease 2019 (COVID‐19) pandemic has resulted in older adults living alone in social isolation. The purpose of the study was to describe the meaning of the experience of Filipino older adults, who are living alone and using social media technologies during the COVID‐19 pandemic. Eight participants who met the inclusion criteria were interviewed using the snowball selection technique. Transcribed interviews were read while also listening to the record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…The findings from three qualitative studies were similar when the informants emphasised the importance of ICTs in making them continue to virtually connect with others during the lockdown period [ 25 , 26 , 27 ]. Social technology applications such as messaging and video calls were part and parcel of their daily life to keep them connected with their family and friends.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…The findings from three qualitative studies were similar when the informants emphasised the importance of ICTs in making them continue to virtually connect with others during the lockdown period [ 25 , 26 , 27 ]. Social technology applications such as messaging and video calls were part and parcel of their daily life to keep them connected with their family and friends.…”
Section: Resultsmentioning
confidence: 83%
“…The summary from the qualitative studies indicated that the pandemic had caused loneliness and a sense of isolation due to the absence of physical contact [ 25 , 26 , 27 ]. However, not all experienced loneliness as some, especially those who are digitally literate, might find that conducting activities virtually are enjoyable and satisfying [ 25 , 27 ]. The COVID-19 pandemic also caused the informants to have difficulty in time management, excessive boredom, sadness, and anxiety [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations